Pengaruh Insentif Dan Motivasi Terhadap Kinerja Karyawan Di PT. Cisarua Mountain Dairy - Wiranto; M. Azis Firdaus; Asti Marlina (CV. ITTC INDONESIA, 2023)
This research was conducted to find out the extent of incentives and motivation on work performance. The sample used in this study were 40 employee respondents at PT. Cisarua Mountain Dairy The method used is to spread the questionnaire form to the respondents and the data is processed using a computer application. This research was conducted at PT. Cisarua Mountain Dairy. Incentive and Motivation Variables on Work Achievement obtained the results of validity test, reliability test, descriptive analysis, inferential statistics, determination, t test, f test, the results of this study showed that partially the incentive variable (X1) had a significant effect on the achievement variable (Y) work at PT. Cisarua Mountain Dairy with t Count > t Table 4.789 > 3.209 and a significance value of 0.000 < 0.003 and Partially the Motivation variable (X2) has a significant effect on the Work Achievement Variable (Y) in PT. Cisarua Mountain Dairy with a t value Count > t Table 3,990 > 2,286 and a significance value of 0.000 < 0.028 Simultaneously, Incentive Variables (X1) and Motivational Variables (X2) have a significant effect on Work Achievement Variables (Y) in PT. Cisarua Mountain Dairy with a value of f Count > f Table= 21.787 > 3.24 and a significant value of 0.000 < 0.005.